Determination and seasonal analysis of physicochemical characterization and metal(oid)s of landfill leachate in Bushehr port along the Persian Gulf. (2nd January 2023) - Mohammadi, Azam; Malakootian, Mohammad; Dobaradaran, Sina; Hashemi, Majid; Jaafarzadeh, Neemat; Parniani, Nasrin
Abstract: This study focused on the investigation of physicochemical characterization and metal(oid)s in landfill leachate of Bushehr port along the Persian Gulf. TDS, BOD5, COD, Hg, and Cd concentrations in fresh leachate were above leachate discharge standards. Significant differences were detected among alkalinity, EC, COD, and Na + levels in various seasons. Furthermore, the high leachate pollution index (LPI) value showed a significant amount of pollutants present in landfill leachate. The results of this study help in understanding the pollution potential of landfill leachate of Bushehr port along the Persian Gulf. Thus, decision-makers should manage landfill leachate to reduce further environmental pollution.